2017
DOI: 10.2147/ndt.s131438
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of duloxetine versus SSRI monotherapy for the treatment of painful physical symptoms in Japanese patients with major depressive disorder: primary analysis

Abstract: ObjectiveThe objective of this study was to assess the effectiveness of duloxetine monotherapy, in comparison with selective serotonin reuptake inhibitor (SSRI) monotherapy, in the treatment of painful physical symptoms (PPS) in Japanese patients with major depressive disorder (MDD) in real-world clinical settings.MethodsThis was a multicenter, 12-week prospective, observational study. This study enrolled MDD patients with at least moderate PPS, defined as a Brief Pain Inventory-Short Form (BPI-SF) average pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
(31 reference statements)
0
15
0
Order By: Relevance
“…Patient disposition, demographics, and baseline characteristics, and information about safety (adverse events, serious adverse events, and discontinuations due to adverse events) are presented in a study by Kuga et al 21 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patient disposition, demographics, and baseline characteristics, and information about safety (adverse events, serious adverse events, and discontinuations due to adverse events) are presented in a study by Kuga et al 21 …”
Section: Resultsmentioning
confidence: 99%
“…Additional details regarding study design and patient selection are presented in the primary study publication. 21 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Harada et al2 in their report were very much aware of this and showed that initially the direct effect of duloxetine on PPS associated with MDD was greater than its indirect effect, whereas later the indirect effect through improvement in depressive symptoms predominated. In our study,3 we were concerned with showing how to optimize the treatment of MDD with PPS. This clinical question led us to plan our study comparing duloxetine and selective serotonin reuptake inhibitors (SSRIs) 3,4…”
mentioning
confidence: 99%
“…In our study,3 we were concerned with showing how to optimize the treatment of MDD with PPS. This clinical question led us to plan our study comparing duloxetine and selective serotonin reuptake inhibitors (SSRIs) 3,4…”
mentioning
confidence: 99%